Photograph Of Pablo Picasso, Olga Kokhlova And Paulo Picasso - Unknown authorUnknown author (NC, 2026)
Photo of Picasso's family near of one aircraft and with members of the company Ballets Russe. From left to right: Ludmilla Schollar, Alice Nikitina, Serge Lifar, Walter Nouvel, Serge Grigoriev, Lubov Tchernicheva, Mme. Trusevich, Picasso's wife Olga Kokhlova, Picasso's son Paulo Picasso, and Pablo Picasso
Droits : Licence indiquee par Wikimedia Commons
Keywords: peinture; peintres; artistes peintres; picasso; photo; archives photographiques; photographie; Art